2017
DOI: 10.1038/srep44815
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols inhibit the growth and virulence properties of Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum plays a key role in creating the pathogenic subgingival biofilm that initiates destructive periodontitis. It is also a common resident of the human gastrointestinal tract and has been associated with inflammatory bowel disease. The aim of the present study was to investigate the effects of green and black tea extracts as well as two of their bioactive components, EGCG and theaflavins, on the growth and virulence properties of F. nucleatum. The tea extracts and components displayed vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 45 publications
0
66
0
2
Order By: Relevance
“…Previously, it was shown that EGCG has antimicrobial effects against a variety of bacteria via a variety of antimicrobial mechanisms (e.g., damage to the bacterial cell membrane, inhibition of fatty acid synthesis, and inhibition of enzyme activity) 42 . EGCG was also shown to inhibit biofilm formation by various bacterial species including Staphylococcus aureus 43 , Staphylococcus epidermidis 43 , Streptococcus mutans 44 , Porphyromonas gingivalis 45 , Pseudomonas aeruginosa 46 , and Fusobacterium nucleatum 47 at sub-minimal inhibitory concentrations for cell growth. Some of these bacteria produce extracellular amyloid fibers like curli 4 , 5 , suggesting that one of the targets of EGCG is amyloid formation as in the case that fiber formation of pathogenic amyloids involved in protein misfolding disorders, including Alzheimer’s and Parkinson’s diseases is inhibited by EGCG 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that EGCG has antimicrobial effects against a variety of bacteria via a variety of antimicrobial mechanisms (e.g., damage to the bacterial cell membrane, inhibition of fatty acid synthesis, and inhibition of enzyme activity) 42 . EGCG was also shown to inhibit biofilm formation by various bacterial species including Staphylococcus aureus 43 , Staphylococcus epidermidis 43 , Streptococcus mutans 44 , Porphyromonas gingivalis 45 , Pseudomonas aeruginosa 46 , and Fusobacterium nucleatum 47 at sub-minimal inhibitory concentrations for cell growth. Some of these bacteria produce extracellular amyloid fibers like curli 4 , 5 , suggesting that one of the targets of EGCG is amyloid formation as in the case that fiber formation of pathogenic amyloids involved in protein misfolding disorders, including Alzheimer’s and Parkinson’s diseases is inhibited by EGCG 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these bacteria produce extracellular amyloid fibers like curli 4 , 5 , suggesting that one of the targets of EGCG is amyloid formation as in the case that fiber formation of pathogenic amyloids involved in protein misfolding disorders, including Alzheimer’s and Parkinson’s diseases is inhibited by EGCG 48 , 49 . In addition, EGCG suppresses several virulence factors (toxins and enzymes) produced by pathogenic bacteria 44 , 47 , 50 . Taken altogether, EGCG has multiple targets for inhibiting biofilm formation and can be applicable to diverse purposes that are not limited to against biofilm-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…These antiadhesive activities may be enhanced by the combined use of grape phenolic compounds and oral probiotics, preventing the progression of periodontal disease [68]. Flavonoids, especially flavan-3-ols and proanthocyanidins from green tea and grape and wine extracts appear to be the most promising candidates to be used in prevention or management of periodontal diseases [63,69]. Although this does not mean that the consumption of flavonoid-enriched foods reduces the risk of progression or prevents CRC, the antibacterial and anti-inflammatory effects of dietary polyphenols with regard to the inhibition of periodontal pathogen activities and the reduction in the host inflammatory and immune responses warrant further studies aimed at identifying the putative activities in relation to their contribution to colorectal carcinogenesis and uses in nutritional interventions for cancer prevention.…”
Section: Effects Of Polyphenols In Crc Through Modulation Of Oral Micmentioning
confidence: 99%
“…Additionally, phenolic compounds have been reported to modulate broad spectrum of pathophysiological processes such as oxidative stress [ 4 , 5 ], mutagenesis [ 6 ], inflammation [ 7 ] or atherosclerosis [ 8 , 9 ]. A lot of phenolic compounds have also been reported to keep antibacterial as well as antiviral effect [ 10 , 11 , 12 ]. Furthermore, there is huge number of articles focused to anticancer properties of phenolics [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%